Tantangan dan Strategi Pendidikan Jasmani Olahraga dan Kesehatan di Sekolah Dasar: Menuju Generasi Aktif dan Sehat - Mulyana, Agus; Salsabila, Farah; Sundari, Marisa Ayu; Sofiyani, Navisa Elsofa; Fajar, Reiza Nurul; Rahayu, Rina; Fujiyanah, Tri Silviya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the challenges and strategies in implementing Physical Education, Sports and Health learning in elementary schools. The research method used in this article is the literature review method. Data collection techniques with the literature review method used are articles published through Google Scholar. The data that has been obtained is then analyzed using descriptive analysis, starting from data collection, needs analysis, formulation of the subject matter to be studied, to conclusion making. The results of the analysis show that training for PJOK teachers to improve their qualifications and competencies in teaching and motivate students is also very important. Increasing the allocation of PJOK time in the elementary school curriculum can provide greater opportunities for students to participate in physical activity. Support from parents and the community should be increased through socialization programs and cooperation with local communities. In addition, the use of digital technology in PJOK learning can increase student motivation and help them master gross motor skills. The implementation of a creative, innovative, and fun PJOK program is also needed to attract students and instill sportsmanship values such as honesty, cooperation, and unyielding spirit